Anemia and associated factors among patients admitted with metabolic syndromes at Worabe Comprehensive Specialized Hospital, Southern Ethiopia: A cross-sectional study. - Abebe Timerga; Kassahun Haile; Samuel Dessu (PLoS ONE, 2022)
Background Anemia is a condition in which the number of red blood cells is inadequate to meet the physiologic needs of the human body oxygen and it is highly prevalent among individuals with metabolic syndromes as a complication in turn speed up the progression and the number of adverse outcomes unless the proper measure is undertaken. Determination of anemia may play a major role in the management and early aversion of complications in an admitted patient with metabolic syndromes. Therefore, this study aimed to determine anemia and its associated factors among patients with admitted metabolic syndromes at Worabe Comprehensive Specialized hospital, Southern Ethiopia from March 1 to May 30, 2021. Methods and materials An institutional-based cross-sectional study design was conducted on 324 adult patients admitted with metabolic syndromes. Structured questionnaires through face-to-face interviews and participants' medical records were used to collect information on determinants related to anemia. A blood sample was collected to determine hematological parameters, biochemical profile, and blood film preparation. Data were analyzed by SPSS version 22. Binary logistic regression analyses were done to identify factors associated with anemia. The p-value was set at <0.05 with a 95% confidence interval of the adjusted odds ratio. Results A total of 324 admitted adult patients with metabolic syndromes were involved. The overall prevalence of anemia among study participants was 25.3% (95%CI: 20.7, 30.2), of which 52.4% had moderate anemia and 56% had microcytic types of anemia. Being alcoholic (AOR = 6.25, 95% CI: (3.05, 12.82)), obese (AOR = 3.34, 95% CI: (1.02, 11.21)), dyslipidemic (AOR = 2.06, 95% CI: (1.02, 4.17)), and diabetic (AOR = 2.61, 95%CI: (1.31, 5.21)) were significantly associated with anemia. Conclusion The prevalence of anemia among patients admitted with metabolic syndrome observed in this study was a moderate public health problem. Taking alcohol, being dyslipidemic, obese and diabetic was significantly associated with anemia. The finding of this study should be taken into consideration to implement preventive interventions on identified factors in study percipients. Taking fruit and vegetable, and promoting physical exercise, routine determination of fasting blood glucose and hemoglobin level in adult admitted metabolic syndromes patients were recommended to minimize the emergence of anemia.